Consumer identities and clothing style confidence: obstacles to frugal fashion and sustainable clothing consumption - Domingo Gil-Gimenez; Gladys Rolo-González; Ernesto Suárez (Revista Galega de Economía)
High levels of textile consumption and waste have made the fashion industry one of the most polluting sectors, highlighting the need to understand the factors influencing clothing consumption. This study aims to develop a comprehensive instrument to measure clothing consumption, adapt the Clothing Style Confidence Scale for use in a Spanish-speaking context, and explore explanatory models of sustainable clothing consumption. Using a convenience sample of 500 participants, including psychology undergraduate students from a Spanish public university, data was collected through an online questionnaire. The new instrument includes four dimensions: quantity of consumption, focus on fashion, focus on quality, and product disposal. The Clothing Style Confidence Scale was adapted through confirmatory factor analysis. Structural equation modeling was used to test a model examining the influence of consumer identities, environmental self-identity, frugal behavior, and clothing style confidence. The model explained 66% of the variance in clothing consumption, with style confidence and wasteful consumer identity as the strongest predictors.